Keabsahan Perjanjian Jual Beli Melalui Penggunaan Rekening Bersama pada Game Online - Helfida Augestira; Merline Eva Lyanthi (Lembaga Pengembangan Kinerja Dosen, 2024)
Online gaming has grown in popularity due to the development of communications and IT. One of the most common payment methods is the use of shared account services. This research has been conducted in provisions used by dissatisfied buyers, as well as the extent to which contracts for the sale and purchase of shared accounts in online games are legal. Payment is most commonly used in shared account services. This paper explores what legal protections exist for dissatisfied buyers of shared accounts on the internet and which sales contracts apply. Legislative analysis is the research methodology. The research data was obtained by studying legal documents and literature. The study shows that if sales contract a joint account in online games meets the legal requirements of Article 1320 of the Civil Code (KUHPerdata), it is theoretically valid. However, a few potential legal problems, such fraud, theft, and default, can surface. Customers should therefore use caution and pick a trustworthy joint account provider before making any online purchases. Buyers who are offended have access to criminal and civil dispute resolution processes.